(untitled) (Journal of the College of Education for Women, 2019)
The sunna has the great effect in building the Islamic civilization, and the formulation of the Islamic thinking. It worked at spreading of soicinces at every district of Islam. The purified sunna represent one of the main monuments of Islam after Quran in clarifying the basics of the human intercommunication, and the divine reality. It comes as an explanation to the myertious accounts in the shariaa and sunna that it has begun to form an intellectual depth of the Mulsims’ life. The importance ofsunna is it is the second source of legislation in Islamic after the holt Quran. It comes only to affirm what have been mentioned already in theHoly Quran, or clarifying what is not clear in the Quran.